2011
DOI: 10.1007/s12033-011-9377-7
|View full text |Cite
|
Sign up to set email alerts
|

A Species-Specific Polymerase Chain Reaction Assay for Rapid and Sensitive Detection of Colletotrichum capsici

Abstract: Colletotrichum capsici is an important fungal species that causes anthracnose in many genera of plants causing severe economic losses worldwide. A primer set was designed based on the sequences of the ribosomal internal transcribed spacer (ITS1 and ITS2) regions for use in a conventional PCR assay. The primer set (CcapF/CcapR) amplified a single product of 394 bp with DNA extracted from 20 Mexican isolates of C. capsici. The specificity of primers was confirmed by the absence of amplified product with DNA of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 30 publications
1
28
0
3
Order By: Relevance
“…showed that all the strains were C. capsici (Table 2). Among the strains, 92% contained the specific sequence of C. capsici (Torres-Calzada et al, 2011) and were designated as variant 1. In total, four variants of C. capsici were identified on the basis of the sequence analysis of species (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…showed that all the strains were C. capsici (Table 2). Among the strains, 92% contained the specific sequence of C. capsici (Torres-Calzada et al, 2011) and were designated as variant 1. In total, four variants of C. capsici were identified on the basis of the sequence analysis of species (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…PCR detection assay was conducted using the genus Colletotrichum specific primer CC1F1 5'ACCTAACTGTTGCTTCGGCG-3' (Chandra et al, 2009) and the species C. capsici specific primer CcapR 5'-CCCAATGCGAGACGAAATG3' (Torres-Calzada et al, 2011), which gave a specific band size of 425 bp. The PCR mixture of 25 µl contained 1 FTA disk, 5 µl of Buffer (Flexer) 5X, 0.5 µl of dNTP (10 nM), 18.42 µl of distilled H2O, 0.5 µl of each primer (5 µm), and 0.08 µl of DNA Go Taq (Promega).…”
Section: Its Amplification and Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…As recent examples, PCR methods for identification of Sclerotium rolfsii (Jeeva et al, 2010) and Colletotrichum capsici (Torres-Calzada et al, 2011) have been developed based in specific sequences of the ITS region. Improved variants of PCR have emerged with higher sensitivity, specificity and throughput and allowing the quantification of fungi in infected plants or environment.…”
Section: Conventional Pcrmentioning
confidence: 99%